Analisis Bentuk Islamophobia Global: Studi Komparasi Antara Indonesia, India dan Perancis - Willi Ashadi (Institut Muslim Cendekia, 2025)
This study seeks to examine the development of Islamophobia around the world following the September 11, 2001 terrorist attacks that destroyed the World Trade Center in the United States and killed 2,977 people. The 9/11 incident triggered a